Obese Adolescents Show Impaired Meal Responses of the Appetite-Regulating Hormones Ghrelin and PYY - Mittelman, Steven D; Klier, Katie; Braun, Sharon; Azen, Colleen; Geffner, Mitchell E; Buchanan, Thomas A (Obesity (Silver Spring, Md.), 2010)
Ghrelin and peptide YY (PYY) stimulate hunger and satiety, respectively. The physiology of these hormones during normal meal intake remains unclear. This study was designed to compare the responses of these two hormones to meal intake between lean and obese Hispanic adolescents. A total of 10 obese and 7 lean Hispanic youth, aged 11–14 years, consumed two mixed meals, one small and one large, during which plasma measurements of active and total ghrelin and total PYY were obtained. Obese subjects tended to consume more calories during the small meal than lean subjects, although this did not reach statistical significance. Intake of the small meal significantly suppressed active ghrelin and stimulated PYY levels in the lean subjects, and these changes were further accentuated by the large meals. In obese subjects, the suppression of active ghrelin and stimulation of PYY by caloric intake were blunted. Interestingly, a paradoxical stimulation of active ghrelin levels was noted during the small meals in both lean and obese subjects. This stimulation was not seen during the larger meals in lean subjects, but remained present in the obese subjects. Thus, meal-related changes in active ghrelin and PYY are blunted in obese as compared to lean Hispanic subjects. This blunting could contribute to the development or worsening of obesity.